2005
DOI: 10.1002/cpp.455
|View full text |Cite
|
Sign up to set email alerts
|

The simulation heuristic and visual imagery in pessimism for future negative events in anxiety

Abstract: A salient feature of clinical anxiety and its disorders is an elevated subjective probability judgement that future negative events will happen to the individual. A neglected area of research is the cognitive mechanisms that might underlie this judgement in patient populations. First, we investigated the ease of being able to simulate imaginary negative events happening to the individual ('the simulation heuristic'). Second, we conducted the first investigation to our knowledge into the possible role of visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…Commenting that contemporary understanding of the simulation heuristic “is still rudimentary,” Kahneman and Tversky called for further research “in a domain that appears exceptionally rich and promising” (p. 204). Although there has been relatively little research on the simulation heuristic during the past 25 years, we will discuss later some interesting explorations of this heuristic in the future thinking of psychopathological populations (e.g., Brown et al 2002; Raune et al 2005; Vaughn & Weary 2002).…”
Section: Episodic Simulation: Delineating a Conceptmentioning
confidence: 99%
“…Commenting that contemporary understanding of the simulation heuristic “is still rudimentary,” Kahneman and Tversky called for further research “in a domain that appears exceptionally rich and promising” (p. 204). Although there has been relatively little research on the simulation heuristic during the past 25 years, we will discuss later some interesting explorations of this heuristic in the future thinking of psychopathological populations (e.g., Brown et al 2002; Raune et al 2005; Vaughn & Weary 2002).…”
Section: Episodic Simulation: Delineating a Conceptmentioning
confidence: 99%
“…There are many other examples of the use of imagery in domains such as planning and decision-making (Anderson, 1983), sports performance (Feltz & Landers, 1983), clinical treatment of phobia (Raune, Macleod, & Holmes, 2005), advertising (Escales & Luce, 2003), health (Sherman, Cialdini, Schwartzman, & Reynolds, 1985) and academic achievement (Pham & Taylor, 1999). This accumulated research demonstrates that our capacity to mentally simulate future events is not just the preserve of daydream and fantastical thinking.…”
Section: Imagined Contactmentioning
confidence: 99%
“…Bentz et al (2004) used a Consider-An-Alternative debiasing strategy (cf. Hirt & Markman, 1995) and found that asking both highly trait-anxious and non-anxious individuals to generate three alternative positive outcomes for a variety of negative scenarios significantly reduced participants’ ratings of event plausibility (see also Hirt, Kardes, & Markman, 2004; Raune, MacLeod, & Holmes, 2005). However, Bentz et al (2009) also demonstrated that generating more alternative outcomes (e.g., five positive outcomes) incurred no additional benefit in debiasing judgments when compared to generating fewer alternative outcomes (e.g., two positive outcomes).…”
Section: Introductionmentioning
confidence: 99%